Challenges and Possible Solutions for Wildlife Conservation in Ethiopia - Dida, Abkiyo (My University, 2021)
Ethiopia is endowed with a large variety of native plant and animal species within its diverse climate and topography. Around 320 mammalian species, including 39 endemics, 918 bird species, including 19 endemics, 240 reptile species (16 endemics), 71 amphibian species (30 endemics), 172 freshwater fish species, including 38 endemics, and more than 1225 insect species have been scientifically reported in Ethiopia. However, Ethiopia's wildlife is in peril right now. Therefore this review was aimed to identify the major challenges of wildlife conservation in Ethiopia and to suggest a possible solution based on the review results. Deforestation, road kills of wildlife along highways, wildlife trafficking, lack of law enforcement, climate change, human-wildlife conflict, and land-use change are the identified challenges of wildlife conservation in Ethiopia. Develop a collaborative approach, invasive species utilization, promote community involvement and awareness creation are the suggested strategy that can bring solutions to the challenges of wildlife conservation.
Keywords: Wildlife conservation; wildlife trafficking; protected area